Moderate dose inhaled corticosteroids plus salmeterol versus higher doses of inhaled corticosteroids in symptomatic asthma. Issue 9 (31st August 2005) - Masoli, M; Weatherall, M; Holt, S; Beasley, R
Abstract : Background: There is uncertainty as to the dose of inhaled corticosteroids (ICS) at which to start concomitant long acting β agonist (LABA) treatment in patients with asthma not adequately controlled by ICS alone. Methods: A meta-analysis was carried out of randomised, double blind clinical trials that compared the efficacy of adding salmeterol to moderate doses of ICS (fluticasone propionate 200 μg/day or equivalent) with increasing the ICS dose by at least twofold in symptomatic adult patients with asthma. The main outcome measures were the number of subjects withdrawn from the study due to asthma and the number of subjects with at least one moderate or severe exacerbation. Results: Twelve studies with a total of 4576 subjects met the inclusion criteria for the analyses. The number of subjects withdrawn due to asthma and with at least one moderate or severe exacerbation was higher in the high dose ICS group (odds ratios 1.58, 95% CI 1.12 to 2.24 and 1.35, 95% CI 1.10 to 1.66, respectively). For the secondary outcome variables (forced expiratory volume in 1 second, morning and evening peak expiratory flow, and daytime β agonist use) there was significantly greater benefit in the salmeterol group. Conclusions: This meta-analysis shows that the addition of salmeterol to moderate doses of ICS (fluticasone 200 μg/day or equivalent) in patients with asthma symptomatic at that dose results in significantly greater clinical benefit than increasing the dose of ICS by twofold or more.